SANCTION OF THE RULE OF CRIMINAL LAW ON THE DRAFT CRIMINAL CODE OF UKRAINE - Mytrofanov, Igor (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: analysis of the peculiarities of constructing sanctions for the norms of criminal law and sanction orders for the unambiguous application of punishments in sentences by judges during the «launch» of the mechanism for implementing the criminal responsibility of persons guilty of crimes provided for by the draft Criminal Code of Ukraine. In this article, in the legal knowledge of the sanction of the norms of criminal law, the following scientific methods were applied: analysis, synthesis, systematization, generalization of theoretical research results. Results: the functional role of the sanction of the norm of criminal law is manifested in its ability to influence the implementation of the obligation not to commit crimes provided for by the Criminal Code of Ukraine. Discussion: regulation of the behavior of participants in public relations is the result of the interaction of elements of the rule of law (rules of conduct and related decrees), which forms the basis for the implementation of a programmed model of behavior using sanctions. At the same time, any legislative exaggeration of the power of criminal sanctions makes it difficult to distinguish between subjective changes in beliefs and reactions to them. At the same time, sanctions are considered as an obligatory structural element of the norms of criminal law, stimulating proper behavior and / or preventing deviant manifestations by fixing the list of means of criminal law. It is concluded that the draft Criminal Code of Ukraine offers us a complex sanction, consisting not only of punishments, but also other criminal legal means of influence. The draft proposes to consider the sanctions as a conglomerate of the decrees of the Special and General Parts of the Criminal Code of Ukraine. This is a special kind of sanctions, which should be considered as a special group of criminal legal sanctions, which is due to the fact that the disposition (in terms of the characteristics of the objective side, the subjective side, the subject, the object of the crime) indicates the social danger of the act, and hence the degree of punishment, and sanctions orders, the norms of criminal law specify (as special orders) sanction procedures in the articles of the General Part of the Criminal Code of Ukraine.